GUIDELINES FOR COMMUNITY SUSTAINABLE RESETTLEMENT MANAGEMENT UNDER NAMTHEUN 2 ELECTRICITY IN KHAMMOUANE PROVINCE, LAO PEOPLE’S DEMOCRATIC REPUBLIC - Onsy, Salika; Areesrisom, Pawinee; Kongtanajaruanun, Raphassorn; Muakyod, Pinnapa; Taokaenchan, Narin; Areesrisom, Koblap (วารสาร มจร พุทธปัญญาปริทรรศน์, 2025)
The objective of this research was to study the resettlement management of communities under the Namtheun 2 electricity, Khammouane Province, Lao People’s Democratic Republic. It is quantitative research. The sample group used in the study was 380 people in the community under the Namtheun 2 electricity, Khammouane Province, Lao PDR. Data were collected using interviews and data analysis using descriptive statistics. The study found that most of the people were female, aged range between 30-39 years old, and had education at junior high school level or below. Mainly engaged in agriculture and most people have household incomes of less than 5,000 baht, with the original residents before entering the community, namely Mueang Khun Kham and Mueang Nakai. The majority were Buddhist and the main economic crops were rice and vegetables, with water and forest resources being considered important resources for the community. Guidelines for community management in all aspects found that people had opinions at a high level of agreement (Mean = 3.73). When considering each aspect, it showed that in all seven aspects, the public had a high level of opinion, namely: operation system (Mean = 3.83), Management Style (Mean = 3.77), Management Structure (Mean = 3.75), Skills, Knowledge, and Abilities (Mean = 3.74), Strategies (Mean = 3.73), Values ​​(Mean = 3.70), and personnel (Mean = 3.69), respectively. People under the Namtheun 2 Electricity had the most problems in community management and infrastructure management. There are also problems with waste and sewage disposal and professional problems of people in the community. In addition, the problem of traditions, cultures, and beliefs in an area that was a crossroads of diverse ethnic groups, including historical armed forces and bases. The project proceeds without a thorough understanding of that background. As a result, the project is unable to achieve the goal of improving the lives of these affected indigenous peoples.